Proceedings of the 2008 ACM Conference on Computer Supported Cooperative Work 2008
DOI: 10.1145/1460563.1460600
|View full text |Cite
|
Sign up to set email alerts
|

The microstructures of social tagging

Abstract: This article presents a rational model developed under the distributed cognition framework that explains how social tags influence knowledge acquisition and adaptation in exploratory ill-defined information tasks. The model provides integrated predictions on the interactions among link selections, use and creation of tags, and the formation of mental categories. The model shows that the quality of tags not only influences search efficiency, but also the quality of mental categories formed during exploratory se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Similar arguments have been made by Fu (2008) who assumes that artifacts created in the use of social software can lead to changes in cognitive schemas.…”
Section: Introductionsupporting
confidence: 61%
“…Similar arguments have been made by Fu (2008) who assumes that artifacts created in the use of social software can lead to changes in cognitive schemas.…”
Section: Introductionsupporting
confidence: 61%
“…This is why participants were required to perform the distractor task before the test phases. The reason for emphasizing secondary memory processes was that they have been found to play a major role in ST (e.g., Fu, 2008;Fu & Dong, 2012). In our future work, we will more specifically focus on the impact of primary memory as a trigger for searching secondary memory by cues from external environment (e.g., Unsworth & Engle, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In an individual perspective, the need to organise information for later personal retrieval has been found as one of the most important motivation for tagging (Gao, 2011). In a social perspective, some recent work (Fu, 2008;Kimmerle et al, 2010) suggested that social tagging supports cognitive and social learning processes. Our research, described in details in section 2.3, is based upon these results.…”
Section: Folksonomies and Social Taggingmentioning
confidence: 99%
“…Within the framework of Cognitive Distributed Systems (DCS), Fu (2008) studied the interactions between the internal and external representations of concepts, tags and documents when a user is engaged in iterative explore-and-comprehend cycles. Their results suggest that (1) the interactions between internal concepts and external tags gradually lead to the sharing and assimilation of conceptual structures and (2) social tagging systems are then a means for social exchange of knowledge structures.…”
Section: Learning Processes Involved In Taggingmentioning
confidence: 99%
See 1 more Smart Citation